CONVEYOR ANALOG OF MATRIX DIFFIE-HELLMAN PROOTOKOL - Beletsky, А.Я.; Beletsky, О.А. (Journal of Information Technologies in Education (ITE), 2013)
A variant of the construction of the matrix analog of Diffie-Hellman based on pipelined binary update secret element used to generate the secret key encryption legalized subscribers open network. In contrast to the classical protocol proposed algorithm is free from the attacks of the "man in the middle."